ANALISIS STRUKTUR PASAR DAN STRATEGI PERSAINGAN PADA TOKO KUE BEPPA JANDA LAPAK MEMEY - Alya Rafeyfa Asyla; Siti Latifaturrohmah (At-Tawazun, Jurnal Ekonomi Syariah, 2026)
Understanding market structures and competitive strategies is important for the sustainability of small and medium-sized enterprises (SMEs) in the culinary sector. Beppa Janda Lapak Memey Cake Shop was selected because it has successfully survived amid intense local market competition. This study aims to analyze the market structure and competitive strategies implemented by the business. This study employed a descriptive qualitative method through interviews, observations, and documentation involving the owner and employees, supported by relevant literature. The findings indicate that the business operates within a market structure that closely resembles perfect competition, where prices are determined by market demand and supply. The competitive strategies adopted include affordable pricing, product innovation, and customer-friendly service. These strategies have proven effective in enhancing customer loyalty and strengthening the business's competitiveness in the local culinary market.